2013
DOI: 10.1681/asn.2012050528
|View full text |Cite
|
Sign up to set email alerts
|

Islet1 Deletion Causes Kidney Agenesis and Hydroureter Resembling CAKUT

Abstract: Islet1 (Isl1) is a transcription factor transiently expressed in a subset of heart and limb progenitors. During studies of limb development, conditional Isl1 deletion produced unexpected kidney abnormalities. Here, we studied the renal expression of Isl1 and whether it has a role in kidney development. In situ hybridization revealed Isl1 expression in the mesenchymal cells surrounding the base of the ureteric bud in mice. Conditional deletion of Isl1 caused kidney agenesis or hypoplasia and hydroureter, a phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…In a recent mouse study, Kaku et al induced conditional Isl1 deletion in the lateral mesoderm using a Hoxb6-Cre driver, and demonstrated that this caused kidney agenesis or hydroureter [ 35 ]. The authors observed transient Isl1 expression between E10.5—E14.5.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent mouse study, Kaku et al induced conditional Isl1 deletion in the lateral mesoderm using a Hoxb6-Cre driver, and demonstrated that this caused kidney agenesis or hydroureter [ 35 ]. The authors observed transient Isl1 expression between E10.5—E14.5.…”
Section: Resultsmentioning
confidence: 99%
“…Cell specification and cell polarity are not eliminated by loss of Yap in the ND Several genes have been implicated in ureter-bladder maturation, affecting either migration of the ND (Gata3, Raldh2, Ret), UB sprouting position (Gata2, Bmp4), formation of a single UB (Gata3, Ret, Slit2, Robo2, Sprouty1, Islet1; see Grieshammer et al, 2004;Basson et al, 2005;Kaku et al, 2013;Hoshi et al, 2012;Jain et al, 2006), defective CND elimination by apoptosis (Rar, Ptprs;Ptprf, RetY1015F, Dlgh1) or defective adhesion between the ND and the cloacal epithelium (EphA4, EphA7, EphrinB2; see Weiss et al, 2014). We looked at the expression of Robo2, Gata3, Sprouty1, Raldh2, Ret, Bmp4, Slit2, Islet1, EphA4, EphA7 and EphrinB2 by in situ hybridization (ISH), but did not detect any significant changes in expression between controls and Yap cKO (supplementary material Fig.…”
Section: Increased Proliferation In Yap Mutant Cndmentioning
confidence: 99%
“…These domains are zinc fingers that coordinate two zinc ions and mediate proteineprotein interactions (Bhati et al, 2008). Studies of diverse vertebrate models have established that the LIM-HD factors are critical for the development of specialized cells in multiple tissue types, including the nervous system (Ericson et al, 1992;Pfaff et al, 1996;Porter et al, 1997;Moreno et al, 2008a,b,c;Deng et al, 2014), the heart (Pandur et al, 2013), the urogenital system (Kobayashi et al, 2004;Kaku et al, 2013), and such endocrine organs such as the pituitary gland (Mullen et al, 2007) and the pancreas (Ahlgren et al, 1997). In the case of the developing vertebrate central nervous system, LIM-HD transcription factors play crucial roles in controlling cell fate specification, survival and differentiation, and axonal projection patterns (Tsuchida et al, 1994;Hobert and Westphal, 2000;Bach, 2000).…”
Section: Lim-hd Transcription Factors In Vertebrate Developmentmentioning
confidence: 99%